Does Urbanisation Promote Consumption of Diverse Diets? A Nigerian Study (Global Journal of Human-Social Science, 2019)
Increasing urban growth is significantly transforming food landscape. However, consumption of a diverse diet is constrained by different factors owing to disparities in extent of access to nutritionally and safe food in most urban areas. This paper using cross-sectional data from 445 urban households in Nigeria, analyses the determinants of dietary diversity using the Berry Index and Quantile regression model. Income of household head, household size and level of urbanisation were important factors that influenced household's consumption of a diverse diet. However, the rate of influence varies in magnitude across quantiles. Results revealed heterogeneous level of dietary diversity across quantiles which suggests disparities in intake of wider varieties of food in urban settings. Suitable policy interventions are identified.
Keywords: dietary diversity; Nigeria; quantile regression; urbanicity; urban households